Mengoptimalkan Aktivitas dan Hasil Belajar Kelas V Menggunakan Model Learning Together Horay - Rahmah Hayati; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to improve learning activities and outcomes using the Learning Together Horay model. This research uses a qualitative approach with the type of Classroom Action Research. Data were obtained through observation and written tests. The results showed that the activities of educators in meetings 1 to 4 increased from a score of 27 to 31. Classically student activity in meetings 1 to 4 increased from 68% to 100%. The learning outcomes of the cognitive aspects in classical terms at meetings 1 to 4 increased from 5% to 89%. The psychomotor aspect of classically at meetings 1 to 4 increased from 68% to 95%. Classically affective aspects at meetings 1 to 4 increased from 21% to 84%. Based on the results of the study, it can be concluded that the use of the Learning Together Horay model can improve mathematics learning activities and outcomes. This research is suggested to be one of the alternatives or references to determine innovative and varied learning models for improving learning activities and outcomes.